Infestação e parasitismo de Leucoptera coffeella (Guérin-Mèneville & Perrottet, 1842) em cafeeiros em transição agroecológica - Marques, Kulian Basil Santa Cecília (2017)
Brazil is the biggest coffee producer in the world, Minas Gerais is the state that has the largest production, being its southern region the largest producer of Coffea arabica. The coffee culture hosts a wide range of arthropods and some constitute key pest of the crop such as leaf miner (Leucoptera coffeella) causing great losses because of the injuries they cause. The population dynamics of this pest varies depending on the region of cultivation, due to biotic and abiotic factors that act in the coffee agro-ecosystem. Natural enemies, especially the microhymenopteran parasitoids play an important role in the regulation of these pests, being indispensable for sustainable agriculture. This study aimed to evaluate the population dynamics, the infestation of the coffee leaf miner and the action of parasitoid wasps as its controller. It was also verified the abundance, richness, diversity, population dynamics and parasitoids parasitism from Braconidae and Eulophidae families in conventional areas and in agroecological transition (conventional to agroecological) in the southern region of Minas Gerais. The experiments were conducted on 24 plots of coffee over four cropping systems, Conventional (CONV) and transition to Organic shaded (T.OSB) and Organic in full sunlight (T.OS) and Without pesticides (T.SAT), with a total area of 6.0 ha in the agrarian reform areas in the municipalities of Campo do Meio and Guapé. Samples were collected for a period of twenty-two months. To evaluate leaf miner infestation were established 10 collection points in each plot, where five plants were chosen at random and had one leaf removed, totalling 50 leaves in each collection. For assessing species richness, abundance, diversity, similarity and between study areas, and leaf miner parasitism rate, 10 leaves were collected with one mine with intact tissue per leaf in each plot, removing one leaf from the third or fourth pair per plant in the upper or middle thirds. This material was kept at ambient laboratory conditions and parasitoids emerged during 40 days were collected. Climatological data were collected. A total of 621 hymenopteran parasitoids were collected, of wich 420 Braconidae and 201 Eulophidae, belonging to three and five different taxa respectively. The data of the parasitoids found in different cultivation systems indicates Orgilus niger and Stiropius reticulatus as promising and well adapted species. It follows that in conventional coffee trees and in agroecological transition in this work the population of leaf miner is endemic and not cause economic damage and that the action of parasitoids possibly contributes to the regulation of this pest, in addition to climatic factors. The results of this study allow us to conclude that coffee systems studied are favourable environments for the maintenance and preservation of hymenopteran parasitoids of the coffee leaf miner.